Farm level and geographic predictors of antibiotic use in Sri Lankan shrimp farms - Munasinghe, Nalaka (Journal of aquatic animal health, 2012)
Black tiger shrimp Penaeus monodon farming is important for Sri Lanka's rural development plans. Consumer confidence is critical for the development and maintenance of export and domestic shrimp markets. Public concern about the use of antimicrobial drugs and chemicals on shrimp farms, however, could threaten market access. We sought to identify high-risk areas and farm-level risk factors for antimicrobial use to inform the core messages and strategic placement of extension programs to help farmers develop best management practices for antimicrobial use. We undertook a survey of 603 operating farms within the Puttalam district over 42 weeks. Lower stocking density and early harvest were associated with a lower risk of antimicrobial use, whereas standard management practices, including water treatment, feed supplements, probiotic use, pond fertilizing, disinfectant use, and pesticide use, were associated with increased risk. Spatial cluster detection found three significant clusters of antimicrobial-using farms. Antimicrobials were more likely to be used in areas with lower farm density. Some of our counterintuitive findings are discussed from a socioecological perspective. A comprehensive understanding of why antimicrobials are used on shrimp farms requires an evaluation of the physical, epidemiological, and socioeconomic factors